2021
DOI: 10.1021/acsomega.1c00917
|View full text |Cite
|
Sign up to set email alerts
|

Development of a HS-SPME/GC-MS Method for the Extraction and Identification of the Volatile Compounds Emitted by Flowers of Tillandsia xiphioides

Abstract: Tillandsia is a genus belonging to the Bromeliaceae family, most of which are epiphytes. The flowers of some of the Tillandsia species are very fragrant, but the volatile composition has been scarcely reported. In this report, we studied the chemical composition of volatile compounds emitted by the flowers of Tillandsia xiphioides using the HS-SPME/GC-MS method. The extraction conditions (fiber, temperature, and time) were optimized using a multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…By using the CAR/PDMS fiber and two extraction methods with different values of extraction time and temperature developed in a previous study, the majority of the volatile compounds emitted by the flowers of Tillandsia species were extracted efficiently. Indeed, it was shown that the CAR/PDMS fiber allowed to extract the maximum of volatile compounds from T. xiphioides flowers compared to PDMS/DVB and DVB/CAR/PDMS fibers; moreover, considering the volatility of analytes affecting the optimal conditions of temperature and duration of extraction, it is necessary to use two extraction methods in order to trap the majority of volatiles emitted by Tillandsia flowers [ 11 ]. After the GC-MS analysis, the profiles of the volatiles emitted by the flowers of the different species studied were compared qualitatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using the CAR/PDMS fiber and two extraction methods with different values of extraction time and temperature developed in a previous study, the majority of the volatile compounds emitted by the flowers of Tillandsia species were extracted efficiently. Indeed, it was shown that the CAR/PDMS fiber allowed to extract the maximum of volatile compounds from T. xiphioides flowers compared to PDMS/DVB and DVB/CAR/PDMS fibers; moreover, considering the volatility of analytes affecting the optimal conditions of temperature and duration of extraction, it is necessary to use two extraction methods in order to trap the majority of volatiles emitted by Tillandsia flowers [ 11 ]. After the GC-MS analysis, the profiles of the volatiles emitted by the flowers of the different species studied were compared qualitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the odor of this group of compounds, monoterpenoid hydrocarbons generally have a spicy and/or resinous odor, oxygenated monoterpenes have a sweet or citrus odor, and sesquiterpenes have a green and floral odor; however, diterpenes are rarely present in floral fragrances due to their low volatility [ 7 ]. Although close in the composition of floral volatiles, the two forms of T. xiphioides present, nevertheless, a slight difference in the intensities of certain compounds, which can affect the floral odor and lead to a difference in odor for the two forms of this species [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study conducted in our laboratory by Mame Lo et al, a HS-SPME/GC-MS method was developed to study the VOCs emitted by the fragrant flowers of three Tillandsia species. First, two extraction methods were developed and allowed the identification of 30 volatile compounds from T. xiphioides [ 26 ]. Then, these two methods were used to study the aromatic profile of T. caliginosa and T. crocata and allowed to identify 65 compounds [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the present study, the two extraction methods developed in our laboratory by Mame Lo et al [ 26 ] were used to obtain the aromatic profiles of 14 species and hybrids of Tillandsia genus, belonging to a different subgenus [ 5 ]. These species are: T. aeranthos , T. bergeri , T. albertiana , T. ixioides , T. ionantha , T. tenuifolia , T. paleacea , T. cacticola , T. lorentziana , T. didisticha , T. bandensis , T. recurvata , hybrids of T. aeranthos and T. bergeri (T. aeranthos x T. bergeri ), and T. aeranthos ‘ uruguay ’, a form of T. aeranthos (see Section 4.1 ).…”
Section: Introductionmentioning
confidence: 99%